United Arab Emirates : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the United Arab Emirates. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that UAE has successfully weathered recent external shocks, because of its large financial buffers, diversified economy, and strong policy response. The economy is starting to recover from the 2015-16 slowdown caused by a decline in oil prices. Growth momentum is expected to strengthen in the next few years, helped by higher oil output, increased public investment, and stepped-up structural reforms. Gradual and growth-friendly fiscal consolidation should resume once the recovery gains momentum to ensure intergenerational equity. Key priorities have been highlighted to raise spending efficiency, continue diversifying revenues, firmly anchor fiscal policy, and improve policy coordination and management of fiscal risks. The report also discusses that realizing the government's Vision 2021 requires strong effort to foster productivity growth and increase the private sector's role in the economy.